Answer: x=-10, y=13
Step-by-step explanation:
![-3x+2y=56\\-5x-2y=24](https://tex.z-dn.net/?f=-3x%2B2y%3D56%5C%5C-5x-2y%3D24)
+2y-2y = 0, eliminating y is much easier. So -3x-5x = -8x and 56+24 = 80
![-8x=80\\x=-10](https://tex.z-dn.net/?f=-8x%3D80%5C%5Cx%3D-10)
Substitute x in any equations but only 1 equation (Don't substitute in both equations.)
For me, I'd substitute x in -3x+2y=50
![-3(-10)+2y=56\\30+2y=56\\2y=56-30\\2y=26\\y=13](https://tex.z-dn.net/?f=-3%28-10%29%2B2y%3D56%5C%5C30%2B2y%3D56%5C%5C2y%3D56-30%5C%5C2y%3D26%5C%5Cy%3D13)
So the answer is x = -10, y = 13
How much after subtraction
Answer:
Remember if cosecθ=1/sinθ
sinθ×cosecθ=sinθ×1/sinθ=1
CMIIW
Answer:
(2.5, -1)
(-2.5, 1)
(-1, 2.5)
Step-by-step explanation:
Answer:
The answer is 16
Step-by-step explanation:
2 + 2 is 4 because it's in brackets
8 ÷ 2 is 4
Since they are together this means you have to multiply them.
So 4 × 4 is 16.